Competitiveness of Indonesian Essential Oils in The International Market - Al Fikri, Muhammad Ziyad; Nurfadillah, Suryani; Imam Santoso, Siswanto (SOCA: Jurnal Sosial Ekonomi Pertanian, 2024)
The limitation of technology poses a challenge in the essential oil industry in Indonesia. Indonesian essential oils are still exported in crude form, thus possessing low value-added. Meanwhile, Indonesia has 40 types of essential oils out of 80 traded globally, with 12 of them entering the global commercial market. Therefore, this research is intriguing to examine, aiming to 1) analyze the global market structure of essential oils, 2) analyze comparative competitiveness, and 3) the competitive advantage of Indonesian essential oils. The data consists of secondary data in the form of time series for the period 2012-2022. The data were analyzed using the Herfindahl Index, CR4, RCA, and EPD methods. The research findings indicate that the market structure of essential oils in the international market is oligopolistic with moderate concentration levels. Indonesia has a comparative advantage and strong competitiveness in all countries in this study. The condition of competitive advantage that occurred frequently during the period 2012-2022 in the five target countries is as follows: retreat, followed by rising star, then lost opportunity, and the least occurring is falling star